A Three-Genes Signature Predicting Colorectal Cancer Relapse Reveals LEMD1 Promoting CRC Cells Migration by RhoA/ROCK1 Signaling Pathway - Zhang, Hui; Xu, Chenxin; Jiang, Feng; Feng, Jifeng (Frontiers in Oncology, 2022)
Objective: Colorectal cancer (CRC) experiencing early relapse consistently exhibited poor survival. However, an eﬀective method for the diagnosis and prognosis of CRC postoperative relapse has not been developed. Methods: Multiple datasets from the GEO database and TCGA database were utilized for bioinformatic analysis. The WGCNA analysis and RRA analysis were performed to identity key genes. The COX/Lasso regression model was used to construct the recurrence model. Subsequent in vitro experiments further validated the potential role of hub gene in CRC. Results: A comprehensive analysis was performed on multiple CRC datasets and a CRC recurrence model composing of LEMD1, SERPINE1, and SIAE was constructed. After further validation in two independent databases, we selected LEMD1 for in vitro experiments and found that LEMD1 could regulate CRC cell proliferation, migration, invasion and promote EMT transition. Rho-GTPase pulldown experiments further proved that LEMD1 could affect the activity of RhoA and regulate the cytoskeletal dynamics. We finally demonstrated that LEMD1 promoted CRC cell migration by RhoA/ROCK1 signaling pathway. Conclusion: In this study, a CRC relapse model composing of LEMD1, SERPINE1, and SIAE was constructed by comprehensive analysis of multiple CRC datasets. LEMD1 could promote CRC cell migration through the RhoA/ROCK signaling pathway.